PENGARUH KUALITAS PELAYANANTERHADAP KEPUASAN KONSUMEN INDOMARET KOTA BUKIT PURWAKARTA - ., Muliawan; ., Muhlis (Sekolah Tinggi Ilmu Ekonomi Dewantara, 2018)
The presence of Alfamart near Indomaret which has been standing, it will cause a scramble for customers between Indomart and Alfamart. This is happen at Indomaret of Kota Bukit Purwakarta that caused a decline in the average number of customers per day which shopping. On 2006 Indomaret at Kota Bukit has decreased that significantly by 22.22% compared to the average number of daily customers of 2005. The condition of latest, the average number of daily customers on 2007 (Januari-April) is decreasing as much as 1.20% compared to the average daily benefit of 2006. The research aims to understand the influence of the quality of service for customer satisfaction at Indomaret of Kota Bukit Purwakarta with full and simultaneous. The population that used is the customers Indomaret of Kota Bukit Purwakarta and sample is taken using Slovin formulas with the levels of trust 90%. The data analyze is used Multiple Linier Regression. The result of the research is to inform the quality of service which includes the tangible, realibility, responsive, assurance and empathy to depend on the particular satisfaction simultaneously. Responsive variable is variable which influence with full and has the biggest impact on customers satisfaction Indomaret of Kota Bukit Purwakarta.